ICT innovation: A bridge between farmers and the web - Koigi, Bob (Technical Centre for Agricultural and Rural Cooperation, 2012)
Kenyan farmer, Zack Matere, searches the web for useful agricultural information, then posts it on notice boards around his community helping other producers to improve their crops.